Turkish Political changes TowardsThe Kurdish problem 1999-2006 - Nawal A.Sultan (دراسات أقليمية, 2007)
The research highlights the Changes of the Kurdish problem in Turkey in the aftermath of Abdulla Ocalan's arrest, the leader of PKK.It deals with the most Significant aspects of the problem from the point of view of Turkish Politicans and its reflections upon the practical reality inside the Turkish Society especially the areas inhabited by Kurdish majority. The Research also talks about the strategic aim of PKK. In getting an independent state and Calling for the democratic rights (Political, Cultural and Economic) to reach possible answers for the Problem. The aim has got a regional Support and it was clear in Turkey's Seeking after the accession of E.U. The Kurdish Problem was one of the most Significant Points facing the Turkish government which needs – radical answers in regards to the Turkish Politics.